Sosiopreneurship Berbasis Inovasi Produk Lokal Kopi Daun Kelor Kelopi On Wheels - Virnanda Septiana Putri; Ahmad Fikri Aryaputra; Anik Widiastuti (CV. ALIM'SPUBLISHING, 2026)
. Sociopreneurship has become a strategic concept in inclusive economic development in Indonesia, particularly in integrating social missions with sustainable business models. This article aims to examine the implementation of sociopreneurship at Kelopi On Wheels through the innovation of coffee made from Moringa oleifera leaves, which has proven to be able to increase community empowerment, especially women's farmer groups (KWT), and provide tangible socio-economic impacts for local communities. This research uses a descriptive qualitative approach with documentation study methods and in-depth interviews with the founder of Kelopi On Wheels as the main informant. The results of the study indicate that Kelopi On Wheels has succeeded in developing an innovative product based on local potential that combines coffee drink trends with a healthy lifestyle, while addressing social issues such as stunting and low nutritional consumption in the community. A strategic partnership with KWT Nglipar Village, Gunungkidul Regency, strengthens the inclusive value chain in the supply of raw materials. Despite facing challenges such as low consumer literacy and market preference for conventional coffee, the social innovation promoted by Kelopi On Wheels serves as a relevant and replicable sociopreneurship model in the context of community-based economic development.